BTS clinical statement for the diagnosis and management of ocular tuberculosis. Issue 1 (4th April 2022) - Kon, Onn Min; Beare, Nicholas; Connell, David; Damato, Erika; Gorsuch, Thomas; Hagan, Guy; Perrin, Felicity; Petrushkin, Harry; Potter, Jessica; Sethi, Charanjit; Stanford, Miles
Abstract : The BTS clinical statement for the diagnosis and management of ocular tuberculosis (TB) draws on the expertise of both TB and and ophthalmic specialists to outline the current understanding of disease pathogenesis, diagnosis and management in adults. Published literature lacks high-quality evidence to inform clinical practice and there is also a paucity of data from animal models to elucidate mechanisms of disease. However, in order to improve and standardise patient care, this statement provides consensus points with the currently available data and agreed best practice.